2022
DOI: 10.1007/s40264-022-01212-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Reasons for Switching or Discontinuing Statin Therapy: A Mixed Methods Study Using Social Media

Abstract: Introduction Statin discontinuation can have major negative health consequences. Studying the reasons for discontinuation can be challenging as traditional data collection methods have limitations. We propose an alternative approach using social media. Methods We used natural language processing and machine learning to extract mentions of discontinuation of statin therapy from an online health forum, WebMD ( http://www.webmd.com ). We then ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Registry have identified patient perceptions and barriers to statin adherence. 6,7,33,34 The present study corroborated some of these previous findings, uncovering similar reasons for statin hesitancy, Because no topics had a positive sentiment, the color map was truncated at 0.2 to allow for differentiation between negative and neutral sentiments. 36 Such misperceptions posted on social media platforms can serve as seeds for the spread of misinformation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Registry have identified patient perceptions and barriers to statin adherence. 6,7,33,34 The present study corroborated some of these previous findings, uncovering similar reasons for statin hesitancy, Because no topics had a positive sentiment, the color map was truncated at 0.2 to allow for differentiation between negative and neutral sentiments. 36 Such misperceptions posted on social media platforms can serve as seeds for the spread of misinformation.…”
Section: Discussionsupporting
confidence: 88%
“…For example, the USAGE (Understanding Statin Use in America and Gaps in Patient Education) study and PALM (Patient and Provider Assessment of Lipid Management) Registry have identified patient perceptions and barriers to statin adherence. 6 , 7 , 33 , 34 The present study corroborated some of these previous findings, uncovering similar reasons for statin hesitancy, including adverse effect profiles (eg, myalgias, increased risk of diabetes, and cognitive dysfunction; group 2), disbelief in the LDL-C hypothesis, preference for lifestyle alternatives (eg, dietary or supplementary modifications; groups 1, 3, and 6), and general disenfranchisement with health care (group 5). Furthermore, novel points of discourse were uncovered, such as the role of statins in improving COVID-19 outcomes, controversy regarding lifestyle improvement on a ketogenic diet but developing asymptomatic dyslipidemia, the use of the coronary artery calcium score as a convincing data point for initiating a statin, and hesitancy toward statins because of concerns that statins were made with fetal stem cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…• when other sources of information are not freely available, such as in languages other than English [7,9,19,20,22,38,43,47]; • when researchers investigate questions related to patients and population, while these questions are not discussed with medical doctors or require large population samples. We can mention for instance sentiment analysis on medication and vaccines [7,20,33,38,43,47], and adverse drug effects [76,77]; • when mental health of patients is concerned in cases like depression [9, 4, 78], eating disorders [79], suicide detection and prevention [19,80], quality of life of patients [31,81], and drug misuse [82][83][84].…”
Section: Social Media As the Preferred Source Of Informationmentioning
confidence: 99%
“…Medication nonadherence/discontinuation is an important issue in healthcare worldwide and it is a particular challenge for the treatment of chronic diseases. In the last few years, the role of social media in delivering patients personal experience following drug administration is becoming of great importance since it might influence other patients adherence to medical therapy [7]. Medication nonadherence/discontinuation may result in significant increase in adverse events and healthcare cost [7].…”
mentioning
confidence: 99%